(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present investigation was to evaluate the diagnostic ability of laser fluorescence (LF)-based device and a light emitting diode (LED)-based device regarding the effects of different types of fissure sealants and etching modalities under in vitro conditions.Materials and Methods: All samples (n = 60) were divided into 4 groups. Opaque or clear sealants were applied to the surface of extracted human molar teeth after etching the surface with either acid or laser pretreatment methods. Both the LF-based DIAGNOdent pen device (Kavo, Biberach, Germany) and an LED-based device (Midwest Caries I.D.; Dentsply Professional, York, PA, USA) were used to measure decalcification scores both before and after sealant application and following thermocycling. The Statistical Package for the Social Sciences (SPSS v16.0, IBM, Chicago, IL, USA) was used for statistical analyses. To examine the inter-observer and intra-observer agreements, an intraclass correlation was used. The Wilcoxon test was used to compare the effects of both the sealants and the etching modalities. A p value of 0.05 was accepted as statistically significant. Results: Statistically significant higher readings were achieved with the LED device after applying the opaque sealant in both the acid etched (p = 0.006) and laser treated groups (p = 0.001). The clear sealant did not affect the LF- and LED-based devices’ readings after etching with either acid or the laser. Thermocycling increased the LF readings in the laser etched/clear sealant group, but it did not change the LED-based device’s results.Conclusion: The LF and LED results were not influenced by etching with either acid or a laser on the clear sealant. After the application of an opaque sealant, higher readings on the LED device were achieved for both the laser treated and acid etched groups. Thermocycling did not affect the LED device’s readings.